FABRIKASI DAN KARAKTERISASI GELAS KERAMIK BOROSILIKAT BERBAHAN DASAR ZEOLIT ALAM SEBAGAI SUBSTRAT SEL SURYA - , SUHARTONO, Widya Rosita, S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The solar cell is one of the alternative energy that is booming today. That is because the increase on electrical consumption. The sol ar cell is composed of several layers of material, one of which is commonly called buffer layer or substrate. Substrates are often used in solar cells today are borosilicate glass or ceramic type, this is because the coefficient of thermal expansion borosilicate lower than other types of glass. This study used natural zeolites from Klaten as a basic material because it is containing high levels of silica, sodium tetraborate (Na 2B4O7.10H2O) as a source of boron, sodium carbonate (Na 2CO3) for lowering the melting point and titanium oxide (TiO2) as nucleating agent. Formation of glass ceramics made by sintering method with various sintering temperatures 500 0 C, 600 0 C and 700 0 C as well as variations in hold time 30, 60, 90 dan 120 minutes. From this study it can be seen that the samples of borosilicate which refers to U.S. Patent No.4422965 (SiO2 67,7%, B2O3 11,8% dan Na2O 20,5%) can form a glass phase with the heating temperature at 1200 o C and heating rate 3 o C/minutes and sintered at a temperature of 500 o C, 600 o C, 700 o C did not succeed in forming crystalline borosilicate. Measurement of the coefficient of thermal expansion is done at the time of the sample experienced a sintering process and produces the smallest thermal expansion coefficient of the sample with sinter temperature at 600 o C and 30 minutes hold time, ie -3,06237x10 -5 / o C. The largest thermal expansion coefficient obtained from the sample with sintering temperature at 700Â°C and holding time of 60 minutes, ie 0,000343752/ o C. Shrinkage that occurs at a temperature of 500 o C stable with the largest diameter shrinkage at the time of 120 minutes and a high shrinkage occurred in 90 minutes. Greatest pressure test on samples obtained by sintering temperature of 600 o C and sintering time of 60 minutes is equal to 95,2075 MPa.